2018
DOI: 10.1038/s41419-018-0874-5
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 regulates stability of IL-8 mRNA via interplay between HuR and miR-4312 in PDACs

Abstract: Bcl-2 associated athanogene 3 (BAG3) is highly expressed in pancreatic ductal adenocarcinoma (PDAC), and its high expression appears to be a poor prognostic factor for patients with PDAC. In this study, we show that BAG3 knockdown significantly decreases migration and invasion of PDACs via reduction of interleukine-8 (IL-8) production. BAG3 knockdown regulates IL-8 expression at the posttranscriptional levels via interplay between recruitment of RNA-binding protein HuR and miR-4312. HuR binds to the cis-elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 66 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…For example, circAGO2 impels cancer progression by facilitating HuR-repressed functions on AGO2-miRNA complexes; 23 LncRNA B4GALT1-AS1 attracts HuR to boost osteosarcoma cells migration and stemness by reinforcing YAP transcriptional activity; 24 BAG3 regulates IL-8 mRNA stability through the interplay between HuR and miR-4312 in PDACs. 25 Our study represented that HuR interacted with SEMA4D mRNA and further stabilized its mRNA level in ESCC.…”
Section: Discussionsupporting
confidence: 50%
“…For example, circAGO2 impels cancer progression by facilitating HuR-repressed functions on AGO2-miRNA complexes; 23 LncRNA B4GALT1-AS1 attracts HuR to boost osteosarcoma cells migration and stemness by reinforcing YAP transcriptional activity; 24 BAG3 regulates IL-8 mRNA stability through the interplay between HuR and miR-4312 in PDACs. 25 Our study represented that HuR interacted with SEMA4D mRNA and further stabilized its mRNA level in ESCC.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, Li et al . identified IL-8 as HuR-target in pancreatic ductal adenocarcinoma (PDAC) cells 47 . However, in a previous work 17 , we have demonstrated that IL-8 is not a HuR-target in thyroid cells, and this finding is in agreement with those published by Lebedeva et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Judge et al also reported that the accumulation of ubiquitinated protein after bortezomib treatment was the same in WT and BAG3-deficient cardiomyo-PDAC. This novel pathway links BAG3 expression to enhanced PDAC metastasis (82). In aggregate, these studies support the use of BAG3 as a target for the treatment of patients with PDAC; however, that enthusiasm must be tempered by the recognition that the regulation and function of autophagy in pancreatic cancer are complex and likely require precise targeting (83).…”
Section: Bag3 In Cancermentioning
confidence: 68%